Institutional innovations through increased participation in local education governance the provincial government of Bohol - Medina, Marcia Czarina Corazon M. (Philippine Journal of Public Administration, 2015)
The challenge of having an effective and participative local education governance lies in harmonizing the work of local government units (LGUs), the local Department of Education (DepEd), and other stakeholders. For LGUs and DepEd to complement each other to deliver services more effectively and collaboratively at the grassroots level, ways and mechanisms of expanding local resources for education have to be explored and identified.